The effector program of human CD8 T cells supports tissue remodeling - Delacher, Michael; Schmidleithner, Lisa Maria; Simon, Malte; Stüve, Philipp Florenz; Sanderink, Lieke; Hotz-Wagenblatt, Agnes; Wuttke, Marina; Schambeck, Kathrin; Ruhland, Brigitte; Hofmann, Veronika; Bittner, Sebastian; Ritter, Uwe; et al. (Journal of experimental medicine, 2024)
CD8 T lymphocytes are classically viewed as cytotoxic T cells. Whether human CD8 T cells can, in parallel, induce a tissue regeneration program is poorly understood. Here, antigen-specific assay systems revealed that human CD8 T cells not only mediated cytotoxicity but also promoted tissue remodeling. Activated CD8 T cells could produce the epidermal growth factor receptor (EGFR)-ligand amphiregulin (AREG) and sensitize epithelial cells for enhanced regeneration potential. Blocking the EGFR or the effector cytokines IFN-γ and TNF could inhibit tissue remodeling. This regenerative program enhanced tumor spheroid and stem cell-mediated organoid growth. Using single-cell gene expression analysis, we identified an AREG+, tissue-resident CD8 T cell population in skin and adipose tissue from patients undergoing abdominal wall or abdominoplasty surgery. These tissue-resident CD8 T cells showed a strong TCR clonal relation to blood PD1+TIGIT+ CD8 T cells with tissue remodeling abilities. These findings may help to understand the complex CD8 biology in tumors and could become relevant for the design of therapeutic T cell products.